A new species of the weevil genus Ceutorhynchus Germar from Eastern Mediterranean Turkey (Coleoptera: Curculionidae) - Gültekin, Levent (Zootaxa, 2005)
Ceutorhynchus doganlari sp. n. is described from Eastern Mediterranean Turkish region. Ceutorhynchus doganlari is closely related to C. karamani G. Müller and lives on Alyssum murale Waldst. et Kit.